Tanah Pertanian dalam Perspektif Hukum Islam - Jefri Putri Nugraha (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2017)
One of the problems in agriculture in Indonesia is the problem of agricultural land. There are five land issues in Indonesia, namely: (1) wide narrow farmland ownership; (2) decreased land productivity; (3) the occurrence of land conversion that grew larger for non-agricultural purposes; (4) not yet optimal implementation of commodity mapping related to agro ecosystem; And (5) there is still a lot of sleeping land. The solution of those problems has indeed been initiated and some of them have been implemented. But the solution seems to be a purely technical solution, without incorporating Sharia as a law capable of dealing with such problems. This paper aims to explain the Islamic sharia laws related to agricultural land and agricultural policy in Islam.